PENGARUH KOMPETENSI AUDITOR, SELF EFFICACY, SENIORITAS AUDITOR DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT - luh risa apriliani (UNHI Press, 2021)
Audit judgment is a consideration made by the auditor specify opinion on the result audit that has been carried out based on existing evidence. Research wants to test the effect of auditor competence, self efficacy, seniority, and the cask complexity in the audit judgment. population used in this study this research was conducted on all working auditor at the Bali Province Public Accounting Firm. The method determining the sample use purposive sampling with 54 respondents. Using multiple linear analysis techniques. Auditor competence, senior audit, self efficacy, senior audit has a positive effect on audit judgment, but task complexity has a negative effect on audit judgment.